Trends in the use of household water purifiers with activated carbon components by consumers in Quang Ninh (International Journal of Scientific Research and Management (IJSRM), 2024)
Water is a basic human need, and it plays an important role in maintaining a good life and health. The water pollution and urbanization in Quang Ninh province have promoted the household’s demand for water purifiers, in which activated carbon often serves as an essential raw filter core. This study analyzes the factors that measure the consuming water purifiers with activated charcoal components among Quang Ninh consumers regarding the factors: trends on time, frequency, and payment levels; assessment of the benefits of the water purifier with activated charcoal; factors affecting the users’ choices; and the Quang Ninh consumers’ concerns of water cleaners with active carbon components. These are useful information that helps companies manufacturing and supplying water purifiers to capture real needs, thus offering suitable, efficient, and cost-saving products to consumers.